METHODOLOGY OBJECTIFICATION FORENSIC ACTIVITY AS A FACTOR OF THE PROBATIVE VALUE OF THE RESULT FORENSIC - A. V. Nesterov (Теория и практика судебной экспертизы)
A problem of objectification forensic activity can be solved only through a systematic approach. It is shown that increase the probative value of forensic You can use organizational and legal procedures. In particular, using accreditation, standardization, certification and attestation. The presented results provide ideas for further discussion on the problem.